1982
DOI: 10.1115/1.3245127
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Through a Double Pane Window

Abstract: By finite difference calculations the convective flow in a vertical enclosure heated from a side is investigated. The emphasis in the study is for the flow of air in a window cavity. Detailed plots of the stream patterns and isotherms in a multicellular flow are shown and vertically averaged Nusselt numbers as well as typical local values are given. The calculations compare favorably with the experiments of ElSherbiny, Raithby, and Hollands. A working formula for window spacings is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Lee and Korpela [4] indicate that secondary cells will not form in air-filled cavities of A<12. The increased strength of the primary flow at higher values of Ra will also increase the level of thermal stratification and accordingly the results of 5 stability analysis indicate that secondary cells will disappear as Ra becomes sufficiently large (e.g., [12,14,15,16]). The vertical stratification is always strong, locally, at the ends of the cavity and this, in combination with the additional viscous damping adjacent the end-walls, ensures that secondary cells never form in these locations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and Korpela [4] indicate that secondary cells will not form in air-filled cavities of A<12. The increased strength of the primary flow at higher values of Ra will also increase the level of thermal stratification and accordingly the results of 5 stability analysis indicate that secondary cells will disappear as Ra becomes sufficiently large (e.g., [12,14,15,16]). The vertical stratification is always strong, locally, at the ends of the cavity and this, in combination with the additional viscous damping adjacent the end-walls, ensures that secondary cells never form in these locations.…”
mentioning
confidence: 99%
“…Korpela et al [12] showed that the results of Bergholz [13] could be simplified to predict the 4 critical value of Grashof number at which the onset of secondary cells takes place from the conduction regime. This result, recast as a critical Rayleigh number is:…”
mentioning
confidence: 99%
“…A rigorous analysis of #uid #ows can be found in the book by Padet (1991). Theoretical and numerical studies by Raithby and Wong (1981), de Vahl Davis (1968), Korpela et al (1982) re"ned the resolution of the problem, i.e. the accuracy of heat transfer calculations.…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…Korpela et al 1982, Lee and Korpela 1983, Zhao et al 1997, Lartigue et al 2000. Secondary flow enhances heat transfer through glazing cavities, and may also take part in frame cavities of a certain shape, see Gustavsen and Thue (2007).…”
Section: Heat Transfer Modeling Of Window Frame Cavitiesmentioning
confidence: 99%